PLURALITAS MAKNA BUDAYA DALAM KAJIAN ANTROPOLOGI POSTMODERNISME - Susi Susanti; Mardiyanti; A.Tenri Rama Devi; Kay Ilonka (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article examines the plurality of cultural meaning within the perspective of postmodern anthropology, exploring how postmodern thought has fundamentally transformed the understanding of culture as a non-singular, unstable system of meaning that is always in the process of negotiation. Through a critical literature review approach, this article traces the theoretical contributions of key thinkers such as Clifford Geertz, James Clifford, George Marcus, Michael Fischer, and Homi K. Bhabha in understanding culture as an arena of contested meanings. The findings demonstrate that postmodern approaches in anthropology not only critique the universalism and objectivism of classical ethnography, but also open new epistemological spaces for understanding hybrid, subaltern, and polyphonic identities in contemporary cultural realities. The article concludes that the plurality of cultural meaning is an inherent condition of human existence that must be acknowledged rather than homogenized.